Several reflections on regulated activity within the scope of municipal waste collection from real estate owners (Part I) - Czech, Ewa Katarzyna; Modrzejewski, Artur (Polish Yearbook of Environmental Law, 2012)
Several reflections on regulated activity within the scope of municipal waste collection from real estate owners (Part I)